Development of Agricultural Economic Law : Law Unification over Pluralistic of Social Conditions - Widiastuti, - (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2017)
Cultural diversity of people in a country may result in Law Pluralism practised in asociety. Some of them are traditional law and customs which regulate the life of farmers. Onthe other side, govermentâs responsibility to develop unification of agricultural economic lawis aimed to push the improvement of productivity in agricultural products. However,unification of economic law which is not in accordance with the social conditions, custom, andtraditional law of farmers brings them face to face with law problems. As a result, this affectsnegatively on productivity or causes state law disobedience.Key words: Law Unification, Law Pluralism, Agricultural Law